The future of ESS is bright - Schweika Werner; Lindroos Mats; Zanini Luca; Ekelöf Tord (EPJ Web of Conferences, 2023)
The European Spallation Source ESS has still a huge upgrade potential by using an accelerator ring structure for proton pulse compression that can change the long pulse to a medium pulse structure. Therefore, we consider the performance of a medium pulse structure on the existing ESS target, moderator and neutron instrumentation. A medium proton pulse will enhance the neutron peak brightness of thermal and cold neutrons by about one order of magnitude and even up to two orders of magnitude at shortest wavelengths used at ESS, largely increasing the performance of the ESS instruments for neutron scattering. The arguments for a medium pulse length are that it is best adapted to the resolution requirements of the ESS instruments, the coupled moderator, the typical long instruments; furthermore, that it seems feasible to realise a medium pulse length by advanced, slow extraction from an accelerator ring, and feasible for the rotating tungsten target to take the high-power load. We discuss the implications of a medium proton pulse length and its specific choice for the instrument resolution, and for moderator and target. The proposed upgrade is stimulated by the new project ESSnuSB for a neutrino super beam at ESS and motivated by the synergy effect of using a common pulse compressor ring. The upgrade will be a most economical and efficient path for the ESS to a next higher level from an already world leading long-pulse source, transforming with a medium pulse structure into an even much more powerful, future next generation neutron source.